2012
DOI: 10.1038/nmat3362
|View full text |Cite
|
Sign up to set email alerts
|

The predominant role of collagen in the nucleation, growth, structure and orientation of bone apatite

Abstract: The involvement of collagen in bone biomineralization is commonly admitted, yet its role remains unclear. Here we show that type I collagen in vitro can initiate and orientate the growth of carbonated apatite mineral in the absence of any other vertebrate extracellular matrix molecules of calcifying tissues. We also show that the collagen matrix influences the structural characteristics on the atomic scale, and controls the size and the three-dimensional distribution of apatite at larger length scales. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
491
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(528 citation statements)
references
References 53 publications
25
491
0
12
Order By: Relevance
“…Indeed, previous measurements of ACP and HAP nucleation rates demonstrated α is significantly reduced on collagen relative to its value in solution, leading to greatly enhanced nucleation rates (17). Both the DFS measurements and the MD simulations show that, for the collagenapatite interface, binding energies are hundreds of k B T. Thus, when CDAP nucleates, whether from ACP (45) or OCP, based on the results with collagen alignment on CDAP (100) faces we should expect preferential c-axis alignment both parallel to and orthogonal to the long axis of collagen. Moreover, the local variations in collagen orientation by up to 15°are then consistent with a similar spread in bone apatite c axis, as is observed (22).…”
Section: Results and Analysismentioning
confidence: 84%
“…Indeed, previous measurements of ACP and HAP nucleation rates demonstrated α is significantly reduced on collagen relative to its value in solution, leading to greatly enhanced nucleation rates (17). Both the DFS measurements and the MD simulations show that, for the collagenapatite interface, binding energies are hundreds of k B T. Thus, when CDAP nucleates, whether from ACP (45) or OCP, based on the results with collagen alignment on CDAP (100) faces we should expect preferential c-axis alignment both parallel to and orthogonal to the long axis of collagen. Moreover, the local variations in collagen orientation by up to 15°are then consistent with a similar spread in bone apatite c axis, as is observed (22).…”
Section: Results and Analysismentioning
confidence: 84%
“…Although the bio-mineralization process has been thought to be directed by acidic non-collagenous proteins, such as small integrin-binding ligand N-linked glycoprotein [68], it has been reported that type I collagen can initiate bio-mineralization in the absence of any other extracellular matrix molecules in vitro [69]. Currently, the significance and detailed mechanism of collagen cross-linking in the mineralization process remains unclear; however, it is possible that changes in collagen crosslinking may affect the inorganic phase of bone by controlling mineral nucleation.…”
Section: Collagen Cross-linkingmentioning
confidence: 99%
“…At low concentrations of collagen reconstituted in vitro, the presence of negatively charged noncollagenous proteins can lead to in vivo-like intrafibrillar mineralization; whereas their absence results in the precipitation of extrafibrillar mineral globules 28 . However, at higher tissue-like densities of collagen fibrils, where dense monodispersed fibrils display cholesteric 3D alignment, the formation of intrafibrillar mineral has been shown to be possible without the involvement of noncollagenous proteins, and the morphology of the forming mineral reflects the spatial constraints of the dense collagen matrix 29 . As a consequence, the importance of mineral nucleators may well depend on the tissue suprafibrillar hierarchical architecture.…”
Section: General Inhibition Selective Promotion and Selective Inhibimentioning
confidence: 99%
“…Interfaces [47] Nuclear magnetic resonance spectroscopy* Molecular interactions [29] Subject categories…”
Section: Structures Labelingmentioning
confidence: 99%